Why Is the Woman of Endor Portrayed as a Heroine?. (June 2018) - Kim, Koowon
The most troubling aspect of the episode of Saul visiting the woman of Endor is the positive portrayal of the female medium not only in her ability to bring up Samuel's ghost from the underworld but also in her selfless efforts to restore exhausted Saul to strength after séance . No less troubling is the fact that Samuel's authentic prophecy sits in the narrative frame of necromantic divination that Deuteronomy strongly condemns. To top it off, the invoked Samuel does not accuse Saul of the sin of divination, nor does the narrator appear to condemn the female medium for her role in it. This paper is an attempt at answering these questions. I will argue that to answer these questions properly one needs to differentiates between the two processes involved in necromancy; namely, invocation of a ghost and divination by it. The narrator deliberately makes a distinction between the two in the text, which reflects his two-track approach to the cult of the dead practiced in ancient Israel. The narrator does not condemn the female medium for what she does, namely, invocation. He makes her practically disappear from the séance scene and makes her reappear in the meal scene. He positively portrays her as being successful in her job of bringing up the dead, and as showing kindness and sympathy to the despondent king by providing a meal for him. All this has to do with ancestor cult. The narrator, however, makes necromantic divination look ineffective and condemns Saul for resorting to divination, while presenting the message of Prophet Samuel as being authentic. Thus, the narrator shares the Deuteronomic attitude toward divination and condemns necromancy in 1 Sam 28:3–25, but he accommodates the idea of invoking the dead which was an integral part of ancestor cult.